2005
DOI: 10.1080/0144341042000294877
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences and styles in the use of digital games

Abstract: This paper reports work in progress investigating gender differences and styles in the use of digital games amongst advanced level biology students. It is an elaboration on previous work exploring the relationship between cognitive style and academic performance in Maltese students taking biology at advanced level. In this previous work the cognitive style of 581 (212 male and 369 female) advanced biology students was correlated with their academic performance in five different subjects. Pearson's correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
1
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 32 publications
6
60
1
5
Order By: Relevance
“…In addition these authors show that males achieved better results than females in mental-rotation tests and for females there was no relationship between computer-game experience and mentalrotation ability. Investigating the difference and style of digital games by Maltese students Bonanno and Kommers (2005) found that females preferred puzzle, adventure, fighting, and managerial games and males preferred first person shooters, role playing, sports, and strategy games. These authors argue that such choices indicate the underlying gender-related neurocognitive processes that include perceptual speed, fine motor skills, and sequenced hand movements for females and the visuospatial ability (localization, orientation, and mental rotation), target-directed motor skills and greater risk taking in males.…”
Section: Theoretical Constructsmentioning
confidence: 99%
“…In addition these authors show that males achieved better results than females in mental-rotation tests and for females there was no relationship between computer-game experience and mentalrotation ability. Investigating the difference and style of digital games by Maltese students Bonanno and Kommers (2005) found that females preferred puzzle, adventure, fighting, and managerial games and males preferred first person shooters, role playing, sports, and strategy games. These authors argue that such choices indicate the underlying gender-related neurocognitive processes that include perceptual speed, fine motor skills, and sequenced hand movements for females and the visuospatial ability (localization, orientation, and mental rotation), target-directed motor skills and greater risk taking in males.…”
Section: Theoretical Constructsmentioning
confidence: 99%
“…Despite the popularity of computer games is rising in general, the majority of the medium's audience is still male [6]. As a consequence of that generally greater popularity of computer games amongst males, more males play and they play for longer periods [7,8].…”
Section: Computer Games and Gender Differencesmentioning
confidence: 99%
“…This is due to differing interests and preferences, which are argued to be grounded already in infancy and socialization, but probably also because computer games are mostly designed by males, therefore, including essentially masculine characteristics, a high level of violence, and strong gender stereotypes [3]. While males have been found to prefer strategy, action, adventure, sports, and simulation games, particularly with violent content [16,18], females prefer puzzles, board games, quizzes, role-playing, and adventure, as well as educational games [5,7,14]. The main theme of computer games preferred by boys is contest between good and evil, competition, and winning, whereas girls favor storylines and exploration of game characters' personalities [17].…”
Section: Computer Games and Gender Differencesmentioning
confidence: 99%
“…남학생은 여학생과 비교해 게임을 더 많이, 더 자주 이용할 뿐 아니라 상이한 게임유형을 선호한다 [10]. 또한 여성과 남성은 게임이용 태도도 매 우 상이한 것으로 나타난다 [11].…”
unclassified